2021
DOI: 10.1007/s00415-020-10380-x
|View full text |Cite
|
Sign up to set email alerts
|

Central and peripheral nervous system complications of COVID-19: a prospective tertiary center cohort with 3-month follow-up

Abstract: Objective To systematically describe central (CNS) and peripheral (PNS) nervous system complications in hospitalized COVID-19 patients. Methods We conducted a prospective, consecutive, observational study of adult patients from a tertiary referral center with confirmed COVID-19. All patients were screened daily for neurological and neuropsychiatric symptoms during admission and discharge. Three-month follow-up data were collected using electronic health re… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
68
0
6

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 78 publications
(82 citation statements)
references
References 43 publications
(74 reference statements)
4
68
0
6
Order By: Relevance
“…Persisting signs and symptoms three weeks after the acute covid-19 infection may be associated with several distinct clinical entities: 1) organ injury from the acute disease or its treatment (e.g., lung scarring, complications of intensive care, etc. ), 8 10-12 2) post-viral fatigue syndrome, 13-15 3) prolonged viral shedding, especially in immunosuppressed patients, 16 4) reinfection, and 5) mental factors, such as post-traumatic stress. From the patient’s perspective, all or several of these causes are often intertwined and produce a substantial burden of disease.…”
Section: Introductionmentioning
confidence: 99%
“…Persisting signs and symptoms three weeks after the acute covid-19 infection may be associated with several distinct clinical entities: 1) organ injury from the acute disease or its treatment (e.g., lung scarring, complications of intensive care, etc. ), 8 10-12 2) post-viral fatigue syndrome, 13-15 3) prolonged viral shedding, especially in immunosuppressed patients, 16 4) reinfection, and 5) mental factors, such as post-traumatic stress. From the patient’s perspective, all or several of these causes are often intertwined and produce a substantial burden of disease.…”
Section: Introductionmentioning
confidence: 99%
“…Information relating to the acute phase of illness would therefore help contextualise longer-term studies of this kind, including the generalisability of findings to the wider population. Furthermore, COVID-19 cases without such severe neurological complications but with ongoing fatigue, both in those hospitalised with severe initial COVID-19 and without, would be important groups to study with the same methodologies.It is possible that the fatigue comprehensively demonstrated in this study could at least in part be attributed to protracted hospitalisation [5]. Taboada et al [8] identified length of hospitalisation as a predictor of greater impairment in functional fatigue status; highlighting further the relevance of reporting functional outcomes in fatigue research.…”
mentioning
confidence: 78%
“…It is possible that the fatigue comprehensively demonstrated in this study could at least in part be attributed to protracted hospitalisation [5]. Taboada et al [8] identified length of hospitalisation as a predictor of greater impairment in functional fatigue status; highlighting further the relevance of reporting functional outcomes in fatigue research.…”
mentioning
confidence: 78%
See 1 more Smart Citation
“…The prevalence of neuro-COVID has been reported to vary between studies. Although the prevalence rate of neurological symptoms is estimated to be around 3.5 to 84% among COVID-19 patients, in most cases the SARS-CoV-2 RNA was not detected in the cerebrospinal fluid (CSF) (28,30,31). Among 58 patients with COVID-19 and neurological symptoms, the SARS-CoV-2 RNA was detected in CSF of 2 patients (3.4%).…”
Section: Introductionmentioning
confidence: 99%